2002
DOI: 10.1128/jcm.40.12.4748-4749.2002
|View full text |Cite
|
Sign up to set email alerts
|

New Technique (the NOW Test) for Rapid Detection of Streptococcus pneumoniae in the Nasopharynx

Abstract: Although the NOW test was originally introduced as a rapid pneumococcal antigen detection test for use with urine samples, it was successfully adapted to nasopharyngeal samples in the present study. The sensitivity, specificity, positive predictive value, and negative predictive value of the test were 92.2, 97.7, 95.9, and 95.5%, respectively. These results demonstrate that nasopharyngeal colonization with Streptococcus pneumoniae can be documented within 15 min of sample collection.Streptococcus pneumoniae is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 6 publications
3
11
0
Order By: Relevance
“…Streptococcus pneumoniae in the Nasopharynx Faden et al recently reported the use of the NOW immunochromatographic test to rapidly detect nasopharyngeal colonization with Streptococcus pneumoniae (1). While the specificity of the test in this study was relatively high (97.7%), it is important to be aware that oropharyngeal colonizing bacteria other than S. pneumoniae may also produce positive results with this test.…”
Section: Immunochromatographic Test For Rapid Detection Ofmentioning
confidence: 79%
“…Streptococcus pneumoniae in the Nasopharynx Faden et al recently reported the use of the NOW immunochromatographic test to rapidly detect nasopharyngeal colonization with Streptococcus pneumoniae (1). While the specificity of the test in this study was relatively high (97.7%), it is important to be aware that oropharyngeal colonizing bacteria other than S. pneumoniae may also produce positive results with this test.…”
Section: Immunochromatographic Test For Rapid Detection Ofmentioning
confidence: 79%
“…The Binax NOW test also failed to identify a case of pneumococcal meningitis. The causative agent was detected by PCR alone, suggesting a low bacterial count; the manufacturer specifies a detection limit of about 10 5 CFU/ml in cerebrospinal fluid. Furthermore, urine samples can remain positive for weeks after a pneumococcal infection (39), and the test will be affected if the patient has recently been vaccinated with a pneumococcal vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…The antigen against which the Binax NOW test reacts is a cell wall polysaccharide on S. pneumoniae, which is present in all clinically relevant strains. In this study, middle ear fluid, nasopharyngeal secretions, and cerebrospinal fluid were tested as previously described (10,11,36). The Binax NOW test was also adapted for bone tissue by placing the tissue in a tube with phosphate-buffered saline (1 ml) and vortexing it for 30 s. The sample was thereafter mixed with the reaction buffer as described above.…”
Section: Methodsmentioning
confidence: 99%
“…The test result is not affected by antimicrobial treatment as easily as bacterial culture because the test detects the Cpolysaccharide of S. pneumoniae, which is shared by all pneumococcal serotypes, and does not need living bacteria [9,10]. Previously, two small studies in young children have suggested that the Binax NOW test might be reliable in detection of S. pneumoniae from nasopharyngeal samples [2,11]. However, sampling deeply from the nasopharynx is unpleasant for the patient and not feasible without experience, therefore sampling from the anterior nose would be more realistic in office practice.…”
Section: Introductionmentioning
confidence: 95%
“…meningitis, bacteremia, pneumonia, and acute otitis media. Of these infections, acute otitis media is the most common, affecting roughly 80% of children under three years of age [1,2]. Up to half of the acute otitis media cases are caused by S. pneumoniae [3], which is particularly involved in severe and complicated cases [4,5].…”
Section: Introductionmentioning
confidence: 99%